Identification of Optimal Mouse Models of Systemic Sclerosis by Interspecies Comparative Genomics. Issue 8 (27th July 2016) - Sargent, Jennifer L.; Li, Zhenghui; Aliprantis, Antonios O.; Greenblatt, Matthew; Lemaire, Raphael; Wu, Ming‐hua; Wei, Jun; Taroni, Jaclyn; Harris, Adam; Long, Kristen B.; Burgwin, Chelsea; Artlett, Carol M.; et al.
Abstract : Objective: Understanding the pathogenesis of systemic sclerosis (SSc) is confounded by considerable disease heterogeneity. Animal models of SSc that recapitulate distinct subsets of disease at the molecular level have not been delineated. We applied interspecies comparative analysis of genomic data from multiple mouse models of SSc and patients with SSc to determine which animal models best reflect the SSc intrinsic molecular subsets. Methods: Gene expression measured in skin from mice with sclerodermatous graft‐versus‐host disease (GVHD), bleomycin‐induced fibrosis, Tsk1/+ or Tsk2/+ mice was mapped to human orthologs and compared to SSc skin biopsy–derived gene expression. Transforming growth factor β (TGFβ) activation was assessed using a responsive signature in mice, and tumor necrosis factor receptor superfamily member 12A (TNFRSF12A) expression was measured in SSc patient and mouse skin. Results: Gene expression in skin from mice with sclerodermatous GVHD and bleomycin‐induced fibrosis corresponded to that in SSc patients in the inflammatory molecular subset. In contrast, Tsk2/+ mice showed gene expression corresponding to the fibroproliferative SSc subset. Enrichment of a TGFβ‐responsive signature was observed in both Tsk2/+ mice and mice with bleomycin‐induced skin fibrosis. Expression of TNFRSF12A (the TWEAK receptor/fibroblast growth factor–inducible 14) was elevated in skin from patients with fibroproliferative SSc and the skin of Tsk2/+ mice. Conclusion: This study reveals similarities in cutaneous gene expression between distinct mouse models of SSc and specific molecular subsets of the disease. Different pathways underlie the intrinsic subsets including TGFβ, interleukin‐13 (IL‐13), and IL‐4. We identify a novel target, Tnfrsf12a, with elevated expression in skin from patients with fibroproliferative SSc and Tsk2/+ mice. These findings will inform mechanistic and translational preclinical studies in SSc.